Judges Talking With Children: Legal Terminology Used When Interviewing Taking Statements from Children - Sacau, Ana; Oliveira, Ana; Morais, Joana (Revista de Psicología, 2015)
The purpose of this study was to analyze the legal language used by judges when taking statements from children at court. Despite the existence of national and international regulations on the need to adapt the language to children’s age and level of development, there are few studies that aim to confirm whether this adaptation is real. The analysis of 33 statement takings from children between 8 and 18 years old revealed that judges use a complex legal language when speaking to a child. Forty-eight legal terms were identified. Some of them are similar to those found in other studies carried out in English-speaking countries and with different models of justice (court, testimony or witness). Other terms represent very specific concepts that are difficult to understand for a minor, like provisional suspension of the procedure or confidentiality of judicial inquiries. The presence of legal terminology in the discourse and inquiries that judges use with minors varies considerably among them. The discursive context where these legal terms appear is also complex.